2021
DOI: 10.46245/ijorer.v2i1.75
|View full text |Cite
|
Sign up to set email alerts
|

Design of Learning Activities using Rigorous Mathematical Thinking (RMT) Approach in Application of Derivatives

Abstract: Learning design is one of the factors that support the learning process in order to achieve learning objectives in all subjects including mathematics. Many approaches can be employed by a teacher in making learning design, one of which is rigorous mathematical thinking (RMT) approach. The RMT approach puts forward students actively in constructing their knowledge through the use of psychological tools and mediation. This article reports a set of learning activities designed through a developmental study using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Meanwhile, according to Aulia and Fitriyani (2019), the reasoning is part of rigour mathematical thinking which is a continuation of cognitive processes at a concrete level Several studies have shown that rigorous mathematical thinking is an essential element related to concepts and reasoning. Implementation of rigorous mathematical thinking in students involves construction of mathematical concepts using three cognitive stages, namely cognitive development, content development as a process, and cognitive conceptual construction practices (Dayat Hidayat et al, 2021). Learning practice in this case provides flexibility for students to construct new experiences and knowledge they acquire, while teacher becomes a mediator in utilizing cognitive functions of students in solving math problems.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, according to Aulia and Fitriyani (2019), the reasoning is part of rigour mathematical thinking which is a continuation of cognitive processes at a concrete level Several studies have shown that rigorous mathematical thinking is an essential element related to concepts and reasoning. Implementation of rigorous mathematical thinking in students involves construction of mathematical concepts using three cognitive stages, namely cognitive development, content development as a process, and cognitive conceptual construction practices (Dayat Hidayat et al, 2021). Learning practice in this case provides flexibility for students to construct new experiences and knowledge they acquire, while teacher becomes a mediator in utilizing cognitive functions of students in solving math problems.…”
Section: Discussionmentioning
confidence: 99%
“…This study used qualitative thinking levels to create a design of the learning trajectory where qualitative thinking level consists of 7 indicators that can help students associate between the knowledge they already have and more thoroughly in finding information from the problem. The ability to solve problems is expected to train students in understanding problems, planning strategies to solve problems, solving problems through planning, and checking the results that have been resolved following the level of qualitative thinking levels (Dayat Hidayat et al, 2021). The study aims to develop a learning trajectory on the topic of three-dimensional material geometry to support students' qualitative thinking skills with the RMT approach.…”
Section: Introductionmentioning
confidence: 99%